Changes of cortical epileptic afterdischarges after status epilepticus in immature rats - Tsenov, Grygoriy; Kubová, Hana; Mares, Pavel (Epilepsy research, 2008)
Status epilepticus (SE) in developing rats leads to neuronal degeneration in many brain structures including neocortex but the functional consequences of cortical damage were studied only exceptionally. Lithium-pilocarpine SE was elicited in 12- (P12) and 25-day-old (P25) rats, convulsions were interrupted after 2h by paraldehyde. Cortical electrodes were implanted 3, 6, 9, 13 and/or 26 days after SE. Low-frequency stimulation of sensorimotor cortex was repeated with at least 10-min intervals with a stepwise increasing intensity (0.2-14 mA). Thresholds for movements elicited by stimulation, spike-and-wave afterdischarges (ADs), clonic seizures, mixed ADs (transition into a limbic type of ADs) and recurrent ADs as well as duration of ADs were evaluated. The first three phenomena were not influenced by SE with the exception of lower thresholds for movements during stimulation. Transition into limbic seizures and recurrent seizures were delayed in both age groups and threshold intensities for limbic ADs were at some intervals higher in SE than in control animals. Duration of ADs was changed only at short intervals after SE; it was shortened at 3 and 6 days in P25 and 3 days in P12 rats, respectively. P12 group then exhibited a transient increase in duration of ADs 6 days after SE. Our results did not prove a higher cortical excitability after SE in either age group. On the contrary, there were some signs of a decreased excitability.
Keywords: záchvaty; Electroencephalography; Aging; Male; konvulziva; Rats, Wistar; Lithium Carbonate; longitudinální studie; elektrická stimulace; pohyb; elektroencefalografie; mozková kůra; Electric Stimulation; mužské pohlaví; potkani Wistar; Seizures; lithiumkarbonát; pilokarpin; status epilepticus; krysa rodu Rattus; Pilocarpine; Convulsants; Animals; Epilepsy, Tonic-Clonic; Status Epilepticus; epilepsie tonicko-klonická; zvířata; pohybová aktivita; Movement; Rats; stárnutí; Motor Activity; Longitudinal Studies; Cerebral Cortex